Interpreting Smoke Signals: Fire Ecology and Land Management for Four Federally Listed Birds - Cox, James A.; Engstrom, R. Todd; Breininger, David R.; Hewett Ragheb, Erin L. (Frontiers in Ecology and Evolution, 2020)
Recovery of listed species requires that land managers and research biologists work together to address the factors affecting population stability and growth. In Florida, an essential factor affecting rare species habitat quality and restoration is fire management. Fire plays an essential role in restoring and maintaining almost every upland ecosystem in Florida, but fires also have negative effects (e.g., mortality and displacement) that play out today within an altered landscape where rare species are often limited to small, fragmented areas and negative effects may be accentuated. Fire effects also are complex, not well studied experimentally, and likely to change as urbanization and global temperatures increase over coming decades. These conditions can create missteps in both fire research and fire management without regular communication between scientists and practitioners. We assessed the fire-related research associated with 4 federally listed birds in Florida: Cape Sable seaside sparrow (Ammodramus martimus mirabilis), Florida grasshopper sparrow (A. savannarum floridanus), Florida scrub-jay (Aphelocoma coerulescens), and red-cockaded woodpecker (Dryobates borealis). Fire research has not addressed the needs of some of these species for starkly different reasons. Land managers, in turn, have not successfully applied the recommendations of fire research in other instances. Our results point to fire frequency as an important focus for practitioners managing habitat for rare species in Florida. Our review also suggests that successful integration of research and management will be best served when (1) ecological burning practices are used, (2) local fire management goals are prioritized annually, (3) instructional products are developed for managers, (4) land manager tenure is promoted, (5) stakeholders meet regularly, and (6) creative solutions are devised to overcome staff and equipment shortages.